The Relationship between Students' Problem Posing and Problem Solving Abilities and Beliefs: A Small-Scale Study with Chinese Elementary School Children - Limin, Chen; Van Dooren, Wim; Verschaffel, Lieven (Frontiers of Education in China, 2014)
The goal of the present study is to investigate the relationship between pupils' problem posing and problem solving abilities, their beliefs about problem posing and problem solving, and their general mathematics abilities, in a Chinese context. Five instruments, i.e., a problem posing test, a problem solving test, a problem posing questionnaire, a problem solving questionnaire, and a standard achievement test, were administered to 69 Chinese fifth-grade pupils to assess these five variables and analyze their mutual relationships. Results revealed strong correlations between pupils' problem posing and problem solving abilities and beliefs, and their general mathematical abilities.
Keywords: résolution de problèmes